Qualidade de vida relacionada à saúde de egressos da unidade de acidente vascular cerebral de hospital público de Belo Horizonte: um estudo longitudinal prospectivo - Marcela Aline Fernandes Braga (2022)
Stroke has a great impact on the health of individuals, and therefore, there is a need to assess health-related quality of life (HRQoL). Currently, stroke units (SU) are the reference standards for stroke care. Therefore, the identification of HRQoL predictors in the SU scenario will contribute to the important objectives of the Care Line for Stroke of the Ministry of Health, which presents the national guidelines for the diagnosis, treatment, and follow-up of individuals with this disease. Thus, the general objective of this thesis was to determine the clinical predictors of the generic and specific HRQoL of individuals who graduated from the SU at Hospital Risoleta Tolentino Neves in the city of Belo Horizonte/MG and to compare whether this generic and specific HRQoL, as well as their physical, mental, and social domains, at three, six, and 12 months after hospital discharge change considering the subgroups of disease severity. Three studies were developed to meet this objective and approved by the Research Ethics Committee (CAAE:26431319600005149). The first study aimed to identify acute predictors of generic and specific HRQoL three months after stroke. The second study aimed to identify acute predictors of HRQoL six, and 12 months after hospital discharge. Finally, the third study aimed to compare the generic and specific HRQoL, as well as its physical, mental, and social domains at three, six, and 12 months after hospital discharge, and to verify whether this comparison changed considering the subgroups of the severity of illness. For all studies, individuals with their first stroke and without previous disabilities admitted to the SU of a hospital in the urgency and emergency network in the city of Belo Horizonte were recruited from February 2020 to February 2021 for the sociodemographic and clinical functional characteristics, respectively. Three, six, and 12 months after hospital discharge, participants with preserved cognitive function and without aphasia were assessed by telephone contact regarding generic HRQoL (with the Short Form Health Survey [SF-36]) and specific HRQoL (with the Stroke Specific Quality of Life scale – SSQOL). In the first study, functional independence and age were identified as the only significant predictors of generic (R2=21%; p<0.001) and specific HRQoL (R2=29%; p<0.001) at three months after hospital discharge. As a result of the second study, functional independence was the strongest predictor of generic (R2=14%; p<0.001) and specific (R2=26%; p<0.001) HRQoL at six months and was the strongest predictor of specific HRQoL at 12 months (R2=15%; p<0.001). The strongest predictor of generic HRQoL at 12 months after hospital discharge was sex (R2 = 14 %; p < 0.001). Finally, as a result of the third study, it was observed that different HRQoL outcomes at three, six, and 12 months after hospital discharge showed different behaviors over time between groups of individuals with mild stroke compared to moderate/severe stroke (Interaction:0.004≤p≤=0.034). When considering the generic and specific HRQoL, mental, and social domains, individuals with mild stroke had significantly higher scores than those with moderate/severe stroke three months after hospital discharge. For the physical domain of HRQoL, individuals with mild stroke showed a significant decrease between three and six months after hospital discharge, followed by a significant increase between six and 12 months after hospital discharge, the opposite of what happened in individuals with moderate/severe stroke. Therefore, individuals with mild stroke had better HRQoL in the physical domain than individuals with moderate/severe stroke three and 12 months after hospital discharge. In conclusion, when HRQoL is the outcome of interest, especially for the multidisciplinary team, functional independence should be considered even in the acute phase during hospitalization, given its predictive value at three, six and 12 months after hospital discharge. In addition, the severity of the disease should also be evaluated during hospitalization, since the changes that occur in HRQoL in the first year of the stroke are different according to this severity and, therefore, subjects with different stroke severity require differentiated planning of care to optimize this very complex construct.